Production of green steel from low-grade ores: An end-to-end techno-economic assessment - Alireza Rahbari; M. Shahabuddin; Shabnam Sabah; Geoffrey Brooks; John Pye (Cell Reports Sustainability)
Summary: Hydrogen ironmaking is the most mature and advanced of the available green steel technologies, but uncertainty exists about its cost effectiveness with anything but the highest ore grades. Here, we investigate the end-to-end techno-economics of hydrogen ironmaking in the Australian context. We examine the role of Australian ore grades on the process design, ore beneficiation, fluidized bed (FB) and shaft furnace routes, and downstream steelmaking choices—electric arc furnace or smelter plus basic oxygen furnace (smelter-BOF). We find that low-grade ores have the potential to yield cost-competitive steel through the innovative FB-smelter-BOF pathway, potentially even without ore beneficiation. The cheapest pathway for green steel costs ∼50% more than the conventional blast furnace (BF)-BOF route at a 3.5 USD/kg hydrogen cost. However, after considering market prices for ore and a price on carbon (assumed 90 EUR/tCO2e), green steel appears to be approaching parity with BF-BOF steel at a hydrogen price of ∼4 USD/kg. Science for society: Hydrogen ironmaking is a compelling option for eliminating ∼7% of global emissions arising from iron and steel production. Beyond the high cost of renewable energy, a further challenge persists regarding the removal of impurities, which requires either high-grade ore, extensive ore “beneficiation” processes, or costly fluxing to remove impurities in molten phase. In this paper, these alternatives are evaluated via end-to-end process modeling for a range of ores and processes. Direct reduction ironmaking (DRI) with two-step smelter-basic oxygen furnace (BOF) steelmaking emerges as highly promising, suggesting that lower-grade Pilbara ores will remain competitive in a future decarbonized steel context. In contrast, DRI-electric arc furnace (EAF) single-step processing requires costly higher-grade ores in limited supply or else challenging levels of beneficiation with lower-grade ore. There are major implications for the siting of future green steel and energy infrastructure.